Cervical cancer elimination in Italy: Current scenario and future endeavors for a value based prevention - Calabrò, Giovanna Elisa; Riccardi, Maria Teresa; D'Ambrosio, Floriana; Castagna, Carolina; Sapienza, Martina; Millevolte, Rossella; Pellacchia, Andrea; Ricciardi, Roberto; de Vincenzo, Rosa Pasqualina; de Waure, Chiara (Frontiers in Public Health, 2022)
Background Cervical Cancer (CC) is a vaccine-preventable disease, and it is treatable if diagnosed early and managed properly. However, it is the fourth most common cancer in women worldwide with about 604,127 cases and 341,831 deaths in 2020. In Italy, it represents the fifth most common cancer in women under 50 years of age with about 2,400 new cases in 2020. The CC elimination is today a global public health goal published by the World Health Organization (WHO) in 2020 and a commitment of the European Union that has included it in Europe's Beating Cancer Plan. Therefore, urgent action is needed, at international and national level, to implement value-based interventions regarding vaccination, screening and timely management of the disease. Our study aims to describe the state of the art of Human Papilloma Virus (HPV) prevention in Italy and to get a consensus on indicators for monitoring the progress toward CC elimination at national level. Methods The study envisaged the following activities: research and synthesis of the evidence on strategies and actions for CC elimination at regional Italian level; identification of indicators to monitor such strategies/actions; organization of a multi-stakeholder consensus to reach the agreement on main indicators to be used in Italy. Results As for HPV vaccination coverage, the last Italian available data (December 31st, 2020) showed that it was way below the target (95%) with full cycle vaccination coverage ranging from 6 to 61.7% in female adolescents and from 5.4 to 55.4% in male adolescents (2008 birth cohorts). The coverage rate of CC screening is variable with a range of 61.7–89.6%. Furthermore, coverage rates due to organized screening programs (excluding out-of-pocket screening) shows a range from 20.7 to 71.8%. The mapping of the Italian Regions highlighted an important regional heterogeneity in respect to organizational/operational issue of HPV vaccination and CC screening. Indicators for monitoring CC elimination strategies have been drawn from the Australian experience and distinguished by disease outcomes, vaccination coverage, screening participation and treatment uptake. The highest consensus was reached for the following indicators: CC incidence; detection of high-grade cervical disease; CC mortality; full cycle vaccination coverage; screening participation; high-grade cervical disease treatment rates; CC treatment rates. Conclusions The assessment of the current status of CC elimination as overarching goal beyond the achievement of vaccine, screening and treatment targets represents the first step for the identification of interventions to be implemented to accelerate the path toward CC elimination. Based on this and following the WHO call, a value-based approach is proposed to untangle the full benefit of HPV-related cancers elimination strategies and identify priority and best practices.